2021
DOI: 10.3389/fpls.2021.767984
|View full text |Cite
|
Sign up to set email alerts
|

Integration of mRNA and miRNA Analysis Reveals the Molecular Mechanism of Cotton Response to Salt Stress

Abstract: To identify the regulatory network of known and novel microRNAs (miRNAs) and their targets responding to salt stress, a combined analysis of mRNA libraries, small RNA libraries, and degradome libraries were performed. In this study, we used unique molecular identifiers (UMIs), which are more sensitive, accurate, and reproducible than traditional methods of sequencing, to quantify the number of molecules and correct for amplification bias. We identified a total of 312 cotton miRNAs using seedlings at 0, 1, 3, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Majority of the sRNA reads were unannotated, which possibly attributed to the scarcity of genome information on this species, and implied that numerous sRNAs still remain to be identified in S. apetala. The annotation performed here was in line with previous reports of other plants such as cotton (Zhan et al, 2021) and Ipomoea batatas L. (Yang et al, 2020). Analysis of the length distribution of these sRNA indicated that most were 21-nt and 24-nt (Figure 1), which has also been observed in other mangrove species, including Bruguiera gymnorrhiza and Kandelia (Wen et al, 2016).…”
Section: Small Rna Sequencing and Identification Of Micrornas In Sonn...supporting
confidence: 90%
“…Majority of the sRNA reads were unannotated, which possibly attributed to the scarcity of genome information on this species, and implied that numerous sRNAs still remain to be identified in S. apetala. The annotation performed here was in line with previous reports of other plants such as cotton (Zhan et al, 2021) and Ipomoea batatas L. (Yang et al, 2020). Analysis of the length distribution of these sRNA indicated that most were 21-nt and 24-nt (Figure 1), which has also been observed in other mangrove species, including Bruguiera gymnorrhiza and Kandelia (Wen et al, 2016).…”
Section: Small Rna Sequencing and Identification Of Micrornas In Sonn...supporting
confidence: 90%
“…Osa-mR939 overexpression enhances tillers and early flowering, but reduces the tolerance to salinity and drought stress in Oryza sativa. miRNA396c overexpression enhances NaCl stress tolerance through the mediation of water retention, chlorophylls accumulation, cell membrane Na + /H + , antioxidant enzymes and transcription factors, but reduces the tolerance to alkali and salt stress in Arabidopsis and Oryza sativa (Zhan et al, 2021).…”
Section: Bzip Transcription Factormentioning
confidence: 99%
“…Salinity stress is among the most prominent stresses (abiotic) usually faced by cotton (Gossypium hirsutum) crops around the globe. Salinization hinders the sustainable productivity and development of plants by negatively influencing the metabolic and biological pathways [1]. The increasing amount of NaCl, MgCl 2 , and CaCl 2 as a consequence of many activities, such as wastewater treatment, freshwater channel alterations, or deicing of roads with salt applications is deteriorating the natural environment [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Upland cotton is classified as moderately tolerant to salt and can withstand a saline medium without being significantly harmed, which is comparable to other major cash crops [1,2,15]. Moreover, the cultivars of G. hirsutum vary considerably regarding their tolerance toward salinity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation